Implementation of clinical quality management for rehabilitation in Malaysia - Engkasan, Julia Patrick; Stucki, Gerold; Ali, Sadeeq; Yusof, Yusniza Mohd; Hussain, Hafez; Abdul Latif, Lydia (Foundation for Rehabilitation Information, 2018)
In February 2017, the World Health Organization (WHO) launched its historic”Rehabilitation 2030: A Call for Action”. Scaling up rehabilitation in health systems requires concerted action across all 6 components of WHO's Health Systems Framework. For rehabilitation, information about functioning is essential, as it is required for effective rehabilitation at all levels of the health system. What is missing is a countrywide demonstration project involving the implementation of a clinical quality management system for the continuous improvement of rehabilitation, both at the level of clinical care for individual patients and at the level of rehabilitation service provision. Consequently, the Department of Rehabilitation Medicine at the University of Malaya and University Malaya Medical Centre, together with the Cheras Rehabilitation Hospital of the Ministry of Health, and the Social Security Organisation (SOCSO) Rehabilitation Centre in Malacca, Malaysia, initiated a project to develop a Malaysian-wide clinical quality management system for rehabilitation (CQM-R Malaysia). The objective of this paper is to describe CQM-R Malaysia. First, a conceptual description of a CQM-R based on the International Classification of Functioning, Disability and Health (ICF) is set out. The methods, results and conclusions of a situation analysis conducted in January 2017 are then reported. Finally, the building blocks and implementation action plan developed for CQM-R Malaysia are presented.